Patient Fatigue During Aphasia Treatment: A Survey of Speech-Language Pathologists. (May 2017) - Riley, Ellyn A.
The purpose of this study was to measure speech-language pathologists' (SLPs) perceptions of fatigue in clients with aphasia and identify strategies used to manage client fatigue during speech and language therapy. SLPs completed a short online survey containing a series of questions related to their perceptions of patient fatigue. Of 312 respondents, 80% reported observing fatigue in their patients with aphasia. Notably, 96% of respondents agreed that declining client performance was an indicator of fatigue during sessions. The most commonly reported clinical strategies used when encountering fatigue were taking short breaks and switching to another task. Participants reported that these strategies were primarily selected based on clinical experience (98%) rather than academic or specific clinical training. The study results suggest that current applications of fatigue management are highly variable and that few clinicians base selection of these strategies on any kind of formal training, despite the known importance of this issue.